Strength Analysis of Notch on a Beverage Can Lid by using Finite Element Method - Thanasinsappaya, Tunthanawath; Inban, Samruad (Engineering and Applied Science Research, 2012)
This study was carried out with on objective to analyze the strength of the notch on the lid of abeverage can by finite element method. Influence of the depth of the main score and the anti-fracturescore were studied by constructing a finite-element model of the lid. Depths of the notch was specifiedto be 50%,62.5%,75% and 87.5% of the thickness of the lid. The displacements of the lifting ring wasspecified to be 2,4,6 and 8 mm. The lifting ring was assumed to be made from a rigid material whichthe lid was AA5182 aluminum whose mechanical properties obey the power law of isotropic plastic.The structure of the element was taken as a 10-node tetrahedron and the contact model as surface tosurface model. Results of the analysis revealed that for any displacement value of the lifting ringVon-mises stresses were not uniform over the length of the notch. At 87.5% depth of the main score,the lid was found to have the maximum Von-mises stresses and strains in the vicinity of the rivet.Inthe case of 75% depth of the main score, every displacement value revealed the onset of the damageof the lid. Furthermore, the anti-fracture score influences the stresses and strains of the main score.